Is Lack of Classroom Participation in EFL Classrooms a Sign of Passivity? The Need for a Constructive Pedagogy - ZOUNHIN TOBOULA, Coffi Martinien; OUSSEINI, Hamissou; TANKARI, Moussa (My University, 2022)
The definition of the phenomenon of non-participation in the classroom seems to be subject to several trends. Many educational stakeholders still seem to be divided on the issue of comparing this attitude to passivity. This question was the focus of this exploratory study and adopted a mixed research methods approach. Different data types (quantitative and qualitative) were collected from 282 intermediate EFL learners through a 44-item questionnaire, focus groups, and a case study. Data collected from these students randomly recruited from two universities in the Republic of Benin (UAC: 80, UP: 47) and Niger (UZ: 121, AMU: 34) were analysed using the descriptive interpretation statistical method of SPSS 26 software (quantitative data) and through inductive content analysis method (qualitative data). The results obtained from these different analyses revealed that the lack of class participation could not be systematically considered as a sign of passivity because it is of two kinds (verbal and non-verbal). Moreover, there are two types of passive participation (negative and positive). These findings, among others, showed that this phenomenon is caused by the nature of EFL courses, the learning environment, anxiety, fear of public speaking, and natural cognitive, psychic, psychosomatic, climatic, economic, social, parental, occult (African superstition), and physiological factors. Several recommendations and suggestions were made in light of these findings to prevent this phenomenon.
Keywords: EFL; factors for non-participation; passivity